Causation, Coherence and Concepts - Spohn, W. author. aut Link
XVI, 386 p.
Keywords: In this collection I present 16 of my, I feel, more substantial papers on theoretical philosophy, 12 as originally published, one co-authored with Ulrike Haas-Spohn (Chapter14), one (Chapter 15) that was a brief conference commentary, but is in fact a suitable appendix to Chapter 14, one as a translation of a German paper (Chapter 12), and one newly written for this volume (Chapter 16), which, however, is only my recent attempt to properly and completely express an argument I had given in two earlier papers. I gratefully acknowledge permission of reprint from the relevant publishers at the beginning of each paper. In disciplinary terms the papers cover epistemology, general philosophy of science, philosophy of language, and philosophy of mind. The section titles Belief, Causation, Laws, Coherence, and Concepts and the paper titles give a more adequate impression of the topics dealt with. The papers are tightly connected. I feel they might be even read as unfolding a program, though this program was never fully clear in my mind and still isn’t. In the Introduction I attempt to describe what this program might be, thus drawing a reconstructed red thread, or rather two red threads, through all the papers. This will serve, at the same time, as an overview over the papers collected.